2008
DOI: 10.1523/jneurosci.2772-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Transmembrane Domain 5 as a Critical Molecular Determinant of Menthol Sensitivity in Mammalian TRPA1 Channels

Abstract: TRPA1 is a member of the transient receptor potential (TRP) family of ion channels and is expressed in a subset of nociceptive neurons.An increasing body of evidence suggests that TRPA1 functions as a chemical nocisensor for a variety of reactive chemicals, such as pungent natural compounds and environmental irritants. Activation of TRPA1 by reactive compounds has been demonstrated to be mediated through covalent modification of cytoplasmic cysteines located in the N terminus of the channel, rather than classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
305
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(326 citation statements)
references
References 52 publications
20
305
0
1
Order By: Relevance
“…Menthol's perceptual effects of cooling and sensory irritation have been well studied on the skin and in the mouth, 28,[37][38][39] and a recent investigation showed that menthol sniffed into the nose also produced burning and stinging as well as cooling. 40 Whereas menthol's innocuous cold sensations have been shown to depend on stimulation of the cold-sensitive receptor TRPM8, [41][42][43] its nociceptive sensations appear to arise at least in part from activation of the receptor TRPA1, 44,45 which plays an important role in pain perception, 46 including the sensitivity to painfully cold temperatures. 47 The data from experiment 1 show that when inhaled using the V2 E-cigarette, the coolness produced by 3.5% menthol was the most prominent flavor quality until the highest concentration of nicotine alone produced equal ratings of Overall Sensation.…”
Section: Discussionmentioning
confidence: 99%
“…Menthol's perceptual effects of cooling and sensory irritation have been well studied on the skin and in the mouth, 28,[37][38][39] and a recent investigation showed that menthol sniffed into the nose also produced burning and stinging as well as cooling. 40 Whereas menthol's innocuous cold sensations have been shown to depend on stimulation of the cold-sensitive receptor TRPM8, [41][42][43] its nociceptive sensations appear to arise at least in part from activation of the receptor TRPA1, 44,45 which plays an important role in pain perception, 46 including the sensitivity to painfully cold temperatures. 47 The data from experiment 1 show that when inhaled using the V2 E-cigarette, the coolness produced by 3.5% menthol was the most prominent flavor quality until the highest concentration of nicotine alone produced equal ratings of Overall Sensation.…”
Section: Discussionmentioning
confidence: 99%
“…However, 1-2 mmol l −1 menthol failed to elicit any activity in the leech lN cell (data not shown). This suggests that, similar to Drosophila TRPA1 (Xiao et al, 2008), the TRPA1-like channel in the leech is insensitive to menthol.…”
Section: Effects Of Other Reactive Electrophilesmentioning
confidence: 90%
“…It is worthy to note that menthol is also an agonist of the TRPA1 channel expressed in small DRG neurons (29,30). However, there are several characteristic features of the mode of menthol action on TRPA1 that could be used to discriminate between TRPM8-and TRPA1-mediated menthol responses in sensory neurons.…”
Section: Trpm8 Regulation By G I -Coupled Receptorsmentioning
confidence: 99%